Growth of Physarum flavicomum and Physarum rigidum in Chemically Defined Minimal Media - Henney, Henry R. (1969)
Physarum flavicomum, P. polycephalum, and P. rigidum grew at pH 4.2 in a medium composed of mineral salts, glucose, biotin, thiamine, hematin, and four amino acids. Important differences in pH tolerance were noted among the species. The minimal medium of P. flavicomum and P. polycephalum contained the amino acids methionine, glycine, and arginine, but valine was also required by P. rigidum. Starting with an inoculum of about 0.3 mg of protein per 25 ml of minimal medium, P. flavicomum and P. polycephalum grew to 23 mg and P. rigidum to 12 mg of protein per 25 ml in 3, 2, and 4 weeks, respectively. P. flavicomum and P. polycephalum grew with valine or leucine replacing arginine in the minimal medium but the growth yields and growth rates were decreased. All three species utilized homocysteine thiolactone in the minimal media in place of methionine. Serine adequately replaced glycine for P. rigidum but was inhibitory in the minimal medium of P. flavicomum or P. polycephalum unless homocysteine thiolactone also replaced methionine. Growth rates of all three organisms were increased in the presence of seven amino acids (original four plus leucine, lysine, and isoleucine).